Effect of war on treatment of pulmonary tuberculosis, and evaluation of Directly-observed therapy in Baghdad - Marzook, Ahmed A. (AL-Kindy College Medical Journal, 2011)
Background: Directly observed therapy-short course (DOTS) had been adopted by World Health Organization (WHO) as hopeful strategy for treatment of tuberculosis (TB) since early nineties. Iraqi health authorities started DOTS implementation since 2001 in Baghdad. Coverage expanded gradually till 100% in 2004. War and unstable security condition hit Iraq since March 2003. Objective: The objective of this study was To evaluate the DOTS implementation program in Baghdad in different periods including 2 unstable periods for proper assessment of war and instability on treatment of TB. Patients and methods: This study had been conducted in Baghdad during four different periods (before and during 2003 war, after war; without and with DOTS). Direct interview with patients, and follow up of their treatment were done. Results: The results reveled that78% of patients were in active age groups, 62% of them were males. Surprisingly, direct observation was not achieved in those who were treated under DOTS in the whole periods. Patients treated under DOTS in the 1st and 4th periods showed much better sputum conversion rate after 2 month treatment (88.7 %in 1st and86.5% in 4th periods` patients) than those treated under DOTS during war (45.9% or Non-DOTS 75.6%). A better cure rate also found in patients of both periods (64.9% in 1st and 63% in 4th period) than patients in other periods ( 11% in 2nd% and 43.6% in the 3rd one) .Conclusions: DOTS strategy played important role in improving registration and curing of TB cases in Baghdad. War and unstable security conditions got a destructive effect on treatment of TB patients regardless the followed strategy. Involvement of private medical sector and other governmental and nongovernmental organization can improve TB treatment outcome.